2022
DOI: 10.1038/s42005-022-00805-6
|View full text |Cite
|
Sign up to set email alerts
|

Correlation-driven electronic reconstruction in FeTe1−xSex

Abstract: Electronic correlation is of fundamental importance to high temperature superconductivity. While the low energy electronic states in cuprates are dominantly affected by correlation effects across the phase diagram, observation of correlation-driven changes in fermiology amongst the iron-based superconductors remains rare. Here we present experimental evidence for a correlation-driven reconstruction of the Fermi surface tuned independently by two orthogonal axes of temperature and Se/Te ratio in the iron chalco… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 75 publications
1
8
0
Order By: Relevance
“…In Fe 1+y Te 1−x Se x , angle-resolved photoemission spectroscopy (ARPES) revealed a strong loss of spectral weight of the d xy orbital at high temperatures, which was interpreted in terms of proximity to an orbital-selective Mott transition 35 . Similar drastic changes were also observed as a function of doping 36,37 , mimicking the evolution of spin fluctuations. Nevertheless, the impact of orbital incoherence on nematicity remains little explored 38 .…”
supporting
confidence: 64%
“…In Fe 1+y Te 1−x Se x , angle-resolved photoemission spectroscopy (ARPES) revealed a strong loss of spectral weight of the d xy orbital at high temperatures, which was interpreted in terms of proximity to an orbital-selective Mott transition 35 . Similar drastic changes were also observed as a function of doping 36,37 , mimicking the evolution of spin fluctuations. Nevertheless, the impact of orbital incoherence on nematicity remains little explored 38 .…”
supporting
confidence: 64%
“…This aspect of the crystal structure leads to localization of the Fe 3d xy band as the d xy orbital is confined in the Fe plane 13 , 19 . A recent ARPES study showed a complete loss of coherent spectral weight in the d xy band in FeTe, indicating a strong localization in the band 14 , 20 . The magnetic ground state of FeTe is bicollinear antiferromagnetism (BAFM) as shown in Fig.…”
Section: Resultsmentioning
confidence: 95%
“…The latter allows for the understanding of the existing and emerging strange-metal properties of flat-band systems. Our work also connects the topological flat band systems to the orbital-selective physics of bulk correlated materials ( 28 – 30 ), in which the atomic orbitals exhibit different dispersions and yet [in contrast to models with fully decoupled orbitals ( 31 )] are kinetically coupled with each other.…”
Section: Introductionmentioning
confidence: 99%